Hearing loss in tympanic membrane perforations: an analytic study - Herkal, Kartik; Ramasamy, Karthikeyan; Saxena, Sunil Kumar; Ganesan, Sivaraman; Alexander, Arun (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Tympanic membrane perforations are common cause of hearing loss. There are very few systematic studies that have evaluated the size and location of a perforation to the degree of hearing loss, this study correlates the size and location of tympanic membrane perforation to the pattern of hearing loss. Methods: The study design was based on cross sectional study. Ninety-six ears of dry tympanic membrane perforation of CSOM mucosal type were selected. Photographs of the tympanic membrane perforations were taken and size measured using the “Image J” software. The area of perforation was compared to hearing loss measured by pure tone audiometry. Results: Ninety-six patients, aged 15-60 years with perforated eardrums were studied. Size of tympanic membrane perforation showed moderate level of correlation with hearing loss (Pearson r value=0.463). The various locations of perforations were: posterior (23 ears with Mean hearing loss 28.6±7.7 dB), anterior (31 ears with Mean hearing loss 26.5±7.8dB), subtotal (42 ears with Mean hearing loss 34.2±8.2 dB). Conclusions: The hearing loss is frequency dependent, with maximum hearing loss at lower frequencies. Irrespective of size of perforation the hearing loss was the least for frequency of 2000Hz. Magnitude of hearing loss increases with increase in size of tympanic membrane perforation. Perforation posterior to handle of malleus resulted in more hearing loss than perforations involving anterior to the handle of malleus.